2016
DOI: 10.1186/s40748-016-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mortality and causes of death in Kersa Health and Demographic Surveillance System (Kersa HDSS), Ethiopia, 2008–2013

Abstract: BackgroundIn the world, Neonatal mortality accounts for 40 % of death of children under the age of 5 years. Majority of neonatal deaths occur in developing countries outside of formal health system, among which death in the first hour of first day of their life constitute the huge bulk. This analysis is intended to estimate neonatal mortality rates and identify the leading causes of death based on the surveillance data over 6 years period in Kersa health and demographic surveillance system (Kersa HDSS) site, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 24 publications
11
47
0
Order By: Relevance
“…In the present study, 11.6% of neonates died during followup. We found that most of the deaths occurred during the first (34.0%) and second (61.3%) weeks of neonatal life, which were in line with the previous systematic review studies [7,8] and the studies done in India [32] and Tanzania [33] and also the studies done in Ethiopia [10,[22][23][24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study, 11.6% of neonates died during followup. We found that most of the deaths occurred during the first (34.0%) and second (61.3%) weeks of neonatal life, which were in line with the previous systematic review studies [7,8] and the studies done in India [32] and Tanzania [33] and also the studies done in Ethiopia [10,[22][23][24].…”
Section: Discussionsupporting
confidence: 90%
“…In the study, low birth weight (38.8%) and jaundices (42.9) were the leading causes of death during the early neonatal period, whereas birth asphyxia (72.5%), neonatal sepsis (64.3), and LBW (61.2%) were during late neonatal life in agreement with previous studies [6-8, 32, 33] and the studies done in Ethiopia [22][23][24]. Therefore, this finding indicates that improving the survival of LBW neonates is a particular challenge in the study area, similar to other countries [4,18,25,34].…”
Section: International Journal Of Pediatricssupporting
confidence: 90%
See 2 more Smart Citations
“…Analysis of different studies in Ethiopia showed that the incidence of the neonatal mortality rate was ranged from 17.2 to 35.5 per 1000 live births [10][11][12][13][14][15]. The most determinate factors which were identified by previous studies were birth order, frequency of antenatal care, delivery place, twin delivery and size of neonate [10,16,17].…”
mentioning
confidence: 99%